The porcine piRNA transcriptome response to Senecavirus a infection - Wang, Chen; Chen, Yanxi; Yang, Xiwang; Du, Yunsha; Xu, Zhiwen; Zhou, Yuancheng; Yang, Xu; Wang, Xuetao; Zhang, Chuanming; Li, Shuwei; Yang, Yijun; Li, Wenting; et al. (Frontiers in Veterinary Science, 2023)
Senecavirus A (SVA) belongs to the family of small RNA viruses, the genus Senecavirus, and has become a research hotspot because of the oncolytic viral characteristics. PIWI-interacting RNAs (piRNAs) are a class of small RNAs found in mammalian cells in recent years; however, the host piRNA expression profile during SVA infection and their role in viral infection is not well understood. In this study, we obtained small RNA transcriptome expression profiles from SVA-infected pig kidney cell lines (PK-15) by high-throughput sequencing. Differential expression (DE) analysis, GO annotation, and KEGG analysis of piRNAs in SVA-infected and non-infected PK-15 cells were performed. qRT-PCR was used to validate the DE of piRNAs. The results showed that 981 and 1,370 novel piRNAs were identified in SVA-infected and non-infected PK-15 cells; expression of 129 piRNAs was upregulated while that of 44 piRNAs was downregulated after SVA infection. The DE of 10 piRNAs was further verified by qRT-PCR. GO annotation analysis results showed the metabolism, proliferation, and differentiation were significantly activated after SVA infection. KEGG results showed that after SVA infection, piRNA was mainly enriched in AMPK signaling pathway, Rap1 signaling pathway, circadian rhythm, and VEGF signaling pathway, which suggested that piRNAs may play a role in regulating antiviral immunity, intracellular homeostasis, and tumor processes during SVA infection. This is the first report of the piRNA transcriptome in pig kidney cells and will contribute to the research of piRNA regulatory mechanism during SVA infections and provide an important reference for the prevention and treatment of SVA.